2018
DOI: 10.23736/s0392-9590.18.03950-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exercise on ulcer healing in patients with chronic venous insufficiency

Abstract: A thesis submitted to Imperial College London for the degree of MD(Res)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 194 publications
(229 reference statements)
0
45
0
6
Order By: Relevance
“…More than half ( n = 11) of PA/exercise programmes were conducted in the home environment without supervision 37,38,41,42,44–49,52 . Three studies utilised a small group format ( n = 4 participants per group) that also involved direct supervision by a qualified exercise physiologist 43,47,51 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…More than half ( n = 11) of PA/exercise programmes were conducted in the home environment without supervision 37,38,41,42,44–49,52 . Three studies utilised a small group format ( n = 4 participants per group) that also involved direct supervision by a qualified exercise physiologist 43,47,51 .…”
Section: Resultsmentioning
confidence: 99%
“…For outcomes used to measure VLU healing status, three studies reported time to heal, 18,42,51 six studies reported proportion of ulcer healing, 37,38,42,44,48,51 and nine studies reported rate of changes in the area of ulcer 37–40,42,45,49–51 during the trial period (see Supporting Information S6). One study reported ulcer recurrence rates 51 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations